Exploring the nature of long-term buyer-seller relationships in the Western Australian wine industry - Batt, Peter (Winetitles, 2001)
The nature of the relationship between wineries and wine grape growers is largely one of interdependence; to produce good quality wines, wineries need a reliable supply of good quality grapes. Both the wineries and grape growers report a high degree of trust, satisfaction and commitment in their relationship with their most preferred trading partner. While the wineris exercise the majority of power in the relationship, when accompanied by constant communication that seeks to improve wine quality and to coordinate harvest dates, grape growers are not subjected to any coercive influence strategies that might otherwise undermine the relationship.